Graffiti Culture As Playing Media for Youth In Batang Anai Subdistrict - Muhammad Iqbal; Selvi Kasman; Emzia Fajri (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research discuss about graffiti become playing media for youth in Batang Anai subdistrict. The graffiti is human activity in a culture. The youth graffitiers in Batang Anai create the characters and font in playing graffiti and it as an playing media having certain functions from graffitiers. The purpose of this research is to describe the meaning behind characters and graffiti font as playing media for youth in Batang Anai. The research method in this research is qualitative. The technique of collecting data by doing observation, literature review, interview, and documentation. The writer use semiotics theory by Charles Pierce to analyze meaning and to analyze the function use theory by Robert K. Merton. Based on this research, the conclusion is the meaning characters and graffiti font the youth as graffitiers in Batang Anai such as emoticons, frog’ science, adopt the scorpions way of survival, the birthrate, and abbreviation the real name. The function of graffiti as playing media for youth in Batang Anai such as expression form, the freedom, creativity and social